'Aircraft and pencraft': Between tradition and modernity in arctic varsity exploration. (October 2022) - Bruun, Johanne M.
Abstract: This paper unpacks the material practices and narrative strategies surrounding the aerial work of the 1924 Oxford University Arctic Expedition to Spitsbergen (now Svalbard). Examining the fluid nature of British tropes of polar heroic masculinities, the paper illustrates the adaptability of such tropes in the face of technological change. Specifically, it demonstrates how aviation was mobilised to construct a masculinist explorer subject conceived as simultaneously traditional and modern at a time when the Heroic Era of British exploration was said to have subsided. Significantly, the 1924 expedition was organised largely by and for undergraduate explorers, many of whom saw polar travel as a rite of passage not unlike military service. Hence, the expedition narrative connects to a culture of undergraduate Arctic exploration emerging from Oxbridge during the 1920s. In tracing the 1924 air programme, the paper examines the tensions between polar heroics and new technologies of travel, the significance of nationalist rivalries and failed ambitions in negotiating the status of polar aviation, and problematises the separation of aerial and earth-bound perspectives on polar travel. Focusing on the labour dedicated to bringing aerial technology to the north, the corporeality of the aerial perspective, and iterations of the vertical reciprocity between ground and air, the paper draws out how aircraft was configured both as an instrument for dispassionate observation and as a legitimate vessel for passionate exploration, mirroring and adapting nineteenth century rhetoric of British polar heroics. It is suggested that understanding such historically rooted mechanisms and their adaptability to cultural and technological change remain relevant in terms of contextualising British imaginaries of the Arctic. Highlights: Traces the aerial programme of the 1924 Oxford University Arctic Expedition. Analyses adaptations of heroic travel narratives to technological change. Hones in on cultures of varsity exploration emerging from Oxbridge in the 1920s. Problematises the separation of aerial and earth-bound perspectives on polar travel. Aviation used to form masculinist explorer subject, at once traditional and modern.